The Emotional Dimension of Care in Old Age: The View of Older Adults - Arroyo Rueda, María Concepción; Soto Alanís, Luis Enrique (Cuadernos de Trabajo Social, 2013)
This study shows, from their own perspective, the emotional dimension of men and women aging with illness and dependency. This is a qualitative study with elderly men and women who live in the city and municipality of Durango, Mexico. The data collection techniques were in-depth interviews, participant observation and a personal identification card with socio-demographic data. The results allowed the identification of two types of emotions: dissatisfaction and gratification. Unfortunately, unsatisfactory emotions seem to dominate the life experience of the participants since it is what predominates in the social imagination and in the conversations revolving around this stage of the life cycle. The interaction between the individual and the societal aspects of old age and aging create an emotional stage that determines the actions of older adults. Social Work, together with other disciplines, should reflect from a socio-political stance their participation in changing the perceptions and the negative images of elderly people and promote a new culture of aging.